Editorial: rising rates of venous thromboembolism among hospitalised patients with inflammatory bowel disease in the USA. Issue 7 (7th September 2022) - Bodger, Keith
Abstract : LINKED CONTENT This article is linked to Faye et al papers. To view these articles, visit https://doi.org/10.1111/apt.17162 and https://doi.org/10.1111/apt.17200